Characterization of carbon nanotubes coated monolith synthesized via chemical vapor deposition - Qistina, Omar; Salmiaton, Ali; Choong, Thomas S.Y.; Izhar, Shamsul; Yap, Yun Hin Taufiq (Tamkang University Press, 2024)
Carbon nanotubes (CNTs) have been used as catalyst support in various catalytic activity. The existing CNTs in powder form can create high back pressure and inconvenient operational. Therefore, CNTs coated onto monolith structure provides a promising support for catalyst. In this study, the CNT monolith was synthesized using a chemical vapor deposition (CVD) method with deposition catalyst techniques determined by immersion and impregnation method. The synthesized CNTs monolith were characterized for surface morphology analysis, atomic composition, thermal stability, textural properties, functional group determination and crystallinity. The findings show that the CNTs formed are considered mesoporous nanotubes that attained a diameter size distribution scattered between 30 nm and 35 nm. The carbon yield was successfully achieved at more than 95% by the double immersion in the preparation technique. The CNTs monolith showed a very weak peak due to poor infrared transmittance, while the surface analysis of the CNTs monolith exhibited the type IV isotherm with H3 hysteresis in the presents of mesoporous structures with a relative pressure range of P/Po >0.4. The peak at 2 = 26.46° of the XRD pattern demonstrated a decrease after the synthesizing of CNTs growth onto monolith structure due to the production of carbon. The thermal analysis of the CNTs monolith showed a weight loss of moisture and organic residue of 0.13% and 3%, respectively. The results displayed an optional synthesis method and characterization information of CNTs structured monolith as value added for future production and application.